#### Answer

Next three terms: 65, 62, and 59
Formula:
$a_{1}$=80,
$a_{n}$=$a_{n-1}-3$

#### Work Step by Step

First find the change that is consistent in the problem, by subtracting the second term with the first term, you get $-3$.
You see this change with the third and second term, so on and so forth; $-3$ is a constant change.
We know $a_{1}=80$, all we need now is a formula.
The next term is 3 less than the previous term.
Thus, the formula is: $a_{n}$=$a_{n-1}-3$
Therefore, the next three terms are:
$68-3=65
\\65-3=62
\\62-3=59$